2006
DOI: 10.1007/s10311-006-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromium sorption on grape stalks encapsulated in calcium alginate beads

Abstract: A novel sorbent based on 2% grape stalk wastes encapsulated in calcium alginate beads was investigated for the removal of Cr(VI) and Cr(III) from aqueous solutions. The sorbent proved to be efficient for chromium removal in both hexavalent and trivalent forms from aqueous solution at pH 3.0. In binary mixtures, the presence in solution of one of the forms enhances the sorption of the other which results in an increase of the amount of total chromium removed. This study suggests that the proposed sorbent can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that alginate contains many carboxyl groups, which under strongly acidic conditions, are easily protonated and thus, positively charged [16,17]. The speciation distribution of different Cr(VI) species is shown in Fig.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that alginate contains many carboxyl groups, which under strongly acidic conditions, are easily protonated and thus, positively charged [16,17]. The speciation distribution of different Cr(VI) species is shown in Fig.…”
Section: Effect Of Phmentioning
confidence: 99%
“…It is well documented that alginate beads have been used for the removal of some heavy metal ions including Cr(VI) from solution [16,17]. Moreover, alginate beads are a common and well-known support material in bioscience application for the immobilization of enzymes and living cells, see [18] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“….) are widely investigated [2,[5][6][7]. For instance, aluminosilicates (natural or modified) are being tested for more than 20 years in the removal of toxic metals or organic pollutants [8,9] from aqueous solutions due to favourable surface properties, availability, environmental and economical considerations.…”
Section: Introductionmentioning
confidence: 99%
“…high adsorption capacity of inorganic/organic pollutants. Alginate beads are common and well-known support materials in biosciences applications [1] and are now used in the environmental field [2,3]. Sodium alginate, a water-soluble salt of alginic acid, is a biopolymer and differs from most other polysaccharides exhibiting a sol-gel transition when simply submitted to modification of their ionic environment, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to have potential as an in expensive adsorbent in the development of efficient, clean and cheap technology. It has been satisfactorily applied in the adsorption of heavy metals such as copper [15], nickel and copper [16]-18], lead and cadmium [19], chromium, [20].…”
Section: Introductionmentioning
confidence: 99%